IN HOUSE TRANING TERHADAP PEMBENTUKAN REPUTASI DALAM PENGELOLAAN DANA BUMDES DI DESA LUBUK SAKTI - Firdanianty, Firdanianty; Anggraini, Ferlita (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2020)
In House Training on the Establishment of Reputation in the Management of Village-Owned Enterprises Funds in Lubuk Sakti Village is one of the efforts to create a proper BUMDES financial management and management. This research uses descriptive qualitative through data collection is done by means of observation, documentation and interviews with selected informants. In House Training (Training) is provided using the Focus Group Discussion method and the Training Method. Based on the results of research in the field, it is known that the establishment of the reputation of Village-Owned Enterprises fund managers in Lubuk Sakti Village is still low, this is due to weak human resources, lack of internal coordination, lack of initiative to innovate products and marketing and lack of mastery of technology. So that In House Training is given so that Village-Owned Enterprises managers and Village Apparatuses in Lubuk Sakti Village can move forward and rise.